Volume 4: 20th Design for Manufacturing and the Life Cycle Conference; 9th International Conference on Micro- And Nanosystems 2015
DOI: 10.1115/detc2015-47474
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling Techniques to Forecast Energy Demand in the United States: A Focus on Economic and Demographic Factors

Abstract: Effective energy planning and governmental decision making policies heavily rely on accurate forecast of energy demand. This paper discusses and compares five different forecasting techniques to model energy demand in the United States using economic and demographic factors. Two Artificial Neural Network (ANN) models, two regression analysis models and one autoregressive integrated moving average (ARIMA) model are developed based on historical data from 1950–2013. While ANN model 1 and regression model 1 use G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The results showed that the error of the net consumption of energy consumption obtained via artificial neural network method was very small [15]. Deka (2016) compared five different forecasting technologies using economic and demographic factors to simulate US energy needs with in-depth discussion [16]. Torrini (2016) proposed a fuzzy logic approach to extract rules from input variables and to provide Brazil's long-term annual electricity demand forecast [17].…”
Section: Energy Consumption Forecastmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the error of the net consumption of energy consumption obtained via artificial neural network method was very small [15]. Deka (2016) compared five different forecasting technologies using economic and demographic factors to simulate US energy needs with in-depth discussion [16]. Torrini (2016) proposed a fuzzy logic approach to extract rules from input variables and to provide Brazil's long-term annual electricity demand forecast [17].…”
Section: Energy Consumption Forecastmentioning
confidence: 99%
“…According to the World Population Prospects (2015) [54], the Chinese population will reach 1.424 billion by 2030. Using Equation (16) to calculate the annual growth rate of the population, it can be inferred that the Chinese approximate growth rate of the population from 2016 to 2021 will be 0.25%. Since there is no authoritative estimate of import and export trade in the world, the initial growth rate, average growth rate and minimum growth rate can only be calculated based on historical data of growth.…”
Section: Chinese Primary Energy Consumption Forecasts Based On Differmentioning
confidence: 99%
See 1 more Smart Citation
“…For reduce in carbon emissions from the domestic sector, it is necessary to understand the interaction of the factors which are responsible for each type of energy demand [10]. The theory behind the data to be collected to achieve this understanding is based on well-established building energy modelling principles [11] [12] which show that a building's services energy demand is mainly determined by fabric, area, location, and control. In contrast, occupant energy demand is considered [13] to be driven mainly by the number of occupants, activities undertaken in the building and economic strength.…”
Section: Introduction and Theoretical Approachmentioning
confidence: 99%
“…(1) Time series data is differentiated in order to make it stationary first which is achieved by making both variances and mean constant [10]; (2) Determining p and q orders by studying the autocorrelation and partial autocorrelation coefficients [13,14]; (3) Validating the selected models by applying diagnostic tests that provide information about the residuals being white noise [2,8]. Detail of each of these steps is given under:…”
Section: Autoregressive Integrated Moving Average (Arima) and Holt-wimentioning
confidence: 99%